THE TRIGGERS OF IMPULSIVE BUYING BASED ON BRAND PERSONALITY, SALES PROMOTION, AND SERVICESCAPE USING SHOPPING EMOTION AS MEDIATION OF WARDAH PRODUCTS IN ROXY BANYUWANGI - Qori’atul Adawiyah, Septin Ayu Hapsari (International Journal of Research Science and Management, 2018)
The increasing demand of halal cosmetics products made PT. Paragon Technology Innovation (PTI) developed Wardah cosmetics which is the pioneer of halal cosmetics in Indonesia. Roxy is one of the modern retail outlets in Banyuwangi city which became one of the shopping attractions. Because not everyone makes a purchase, then the first attempt to stimulate the purchase is to make people want to visit the store location. Therefore, retailers implemented promotional strategies to convey promotional information to the public. Promotions are made as interesting as possible so people will actually visit Roxy. Once inside the retail, consumers will be treated with additional information and a convenient physical environment (servicescape) so they are willing to linger.. This triggers impulsive buying to consumers who are interested in sales promotions by retailers. The purpose of this study is to examine the influence between variables, which are: brand personality, sales promotion, servicsape toward impulse buying using shopping emotion as mediation. Based on the research objectives and characteristics of the problems, therefore confirmatory research is used as research method.